2015
DOI: 10.4172/2155-6148.1000536
|View full text |Cite
|
Sign up to set email alerts
|

Post Dural Puncture Headache (PDPH) and Associated Factors after Spinal Anesthesia among Patients in University of Gondar Referral and Teaching Hospital, Gondar, North West Ethiopia

Abstract: Background: Post dural puncture headache (PDPH) has been a problem for patients after dural puncture. It is one of the most frequently occurring complications following spinal anesthesia (SA). It is believed to originate from persistent leakage of cerebrospinal fluid (CSF) through the punctured Dura, greater than the CSF production after lumbar puncture. Although the problem has been widely reported, its magnitude and associated factors has never been studied in our country. Thus, the aim of this study is to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 22 publications
(62 reference statements)
5
15
5
Order By: Relevance
“…According to the findings of this study, the incidence of postdural puncture headache was 28.7%, which is lower than the study conducted at Gondar University Hospital, which showed that 38.8% of PDPH cases occurred (Kassa et al 2015 ). In contrast to this study, another study conducted on factors associated with the onset and persistence of post-lumbar puncture headache in New York showed that the incidence of PDPH is 21.6% during the immediate post procedural period (Monserrate et al 2015 ).…”
Section: Discussioncontrasting
confidence: 62%
“…According to the findings of this study, the incidence of postdural puncture headache was 28.7%, which is lower than the study conducted at Gondar University Hospital, which showed that 38.8% of PDPH cases occurred (Kassa et al 2015 ). In contrast to this study, another study conducted on factors associated with the onset and persistence of post-lumbar puncture headache in New York showed that the incidence of PDPH is 21.6% during the immediate post procedural period (Monserrate et al 2015 ).…”
Section: Discussioncontrasting
confidence: 62%
“…According to the ndings of this study, the incidence of postdural puncture headache was 28.7%, which is lower than the study conducted at Gondar University Hospital, which showed that 38.8% of PDPH cases occurred [19]. In contrast to this study, another study conducted on factors associated with the onset and persistence of post-lumbar puncture headache in New York showed that the incidence of PDPH is 21.6% during the immediate post procedural period [20].…”
Section: Discussioncontrasting
confidence: 73%
“…According to the nding of this study, the incidence of postdural puncture headache was 28.67% which is lower than the study conducted in Gonder University Hospital which showed that 38.8% of PDPH [19]. On contrary to this study, another study conducted on factors associated with the onset and persistence of post-lumbar puncture headache in New York showed incidence of PDPH is 21.6% during immediate post procedural period [20].…”
Section: Discussioncontrasting
confidence: 72%